A comparative analysis of the economic sustainability of cultural work in the UK since the COVID-19 pandemic and examination of universal basic income as a solution for cultural workers - Cécile Doustaly; Vishalakshi Roy (Journal of Risk and Financial Management, 2022)
The COVID-19 pandemic and related lockdowns across the world have greatly affected an already vulnerable cultural economy and the structural precarity of many cultural workers. After documenting the impacts of the pandemic in the cultural sector and the effectiveness of governmental responses in the UK and in Europe, the article focuses on the visual arts and explores calls for reforms of the cultural economy. While the UK government's recovery plan went against the country's cultural policy tradition due to the plan's interventionist and financially generous nature, it disproportionally benefitted organisations rather than individuals working in the sector, especially in England. The study, conducted on visual arts workers in the UK, shows that many were unable to access these financial recovery schemes and fell through the cracks of the complex criteria set for these funds. This article informs the current debate on measures that are potentially more economically sustainable and wellbeing protective than those currently in place for cultural workers, such as Universal Basic Income. Its applicability is explored with reference to the historic French and recent Irish examples.
Keywords: 650; Europe; COVID-19 pandemic recovery plan; cultural and creative industries policy; cultural workers’ precarity; economic sustainability; France; Ireland; UK; Universal Basic Income (UBI); visual arts